1992
DOI: 10.1071/pp9920637
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Carbon Gain and Allocation in Growth at Different Nitrogen Nutrition in Eucalyptus camaldulensis and Eucalyptus globulus Seedlings

Abstract: Potted Eucalyptus camaldulensis and E. globulus seedlings were grown in sand with added mineral nutrients. Mineral nitrogen was added, either (I) only a small initial quantity (N1) or (2) regularly (Nz). Other nutrients were supplied regularly to both treatments. Biomass increment and nutrient concentrations of organs and gas exchange of leaves were measured.Growth, foliage area, and foliar N concentration changed little in Nl seedlings, all increased exponentially in N2 seedlings. Partitioning of dry matter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…While the lower A rates in control seedlings could be attributed to lack of chlorophyll synthesis and activity of photosynthetic enzymes [17,51], a reduction in g s in the presence of environmental stresses is often linked to decline in root water flow and root growth [1,2,10]. Although we did not measure root water flow in the present study, we observed decreased g s , E rates, and less root growth in control seedlings ( Figs.…”
Section: Leaf Physiology and Nutritional Responsescontrasting
confidence: 52%
See 1 more Smart Citation
“…While the lower A rates in control seedlings could be attributed to lack of chlorophyll synthesis and activity of photosynthetic enzymes [17,51], a reduction in g s in the presence of environmental stresses is often linked to decline in root water flow and root growth [1,2,10]. Although we did not measure root water flow in the present study, we observed decreased g s , E rates, and less root growth in control seedlings ( Figs.…”
Section: Leaf Physiology and Nutritional Responsescontrasting
confidence: 52%
“…Nitrogen deficiency often inhibits plant productivity [31,41] by reducing number of leaves, leaf area, and leaf N content [40], ultimately reducing maximum rates of photosynthesis [36]. Photosynthesis is reduced by N deficiency through its effects on chlorophyll synthesis and activity of photosynthetic enzymes [17,51]. Thus, a decrease in leaf N concentration could partly explain the observed chlorosis and lower CI (SPAD readings) in unfertilized plants (Fig.…”
Section: Leaf Physiology and Nutritional Responsesmentioning
confidence: 99%
“…The pH was set to 5.8 and regularly maintained. Walters & Field 1987;Harrington et al 1989, Mulkey et al 1991Reich et al 1991;Hollinger 1992, Lloyd et al 1992Sheri 1992;Thompson et al 1992;Gower et al 1993;DeLucia & Schlesinger 1995;Reich et al 1995aReich et al , 1997; broken lines: PNUE amb estimates from Konings et al 1989;Boot & Den Dubbelden 1990;Pons et al 1994;Atkin et al 1996 Two growth cabinets were used for the experiment, each cabinet divided by black shadecloth into a high light and a low light compartment. All plant species were grown once in each cabinet.…”
Section: Methodsmentioning
confidence: 99%
“…Values of maximum stomatal conductance (g smax ) are also high but appear to vary by at least a factor of two within a species, an observation that is probably linked to the marked response of g s to D referred to in the previous section. As Eucalyptus leaves combine a high capacity for carbon fixation, it is perhaps unsurprising that strong linear relationships are observed between photosynthesis (A) and stomatal conductance (g s ) (Wong et al, 1979) although the slopes of these relationships in Eucalyptus can be affected by species (E. camaldulensis versus E. globulus) and treatment (low versus high nitrogen in E. globulus) (Sheriff, 1992). At very high values of g s in E. nitens, there was no relationship between A and g s .…”
Section: Photosynthesismentioning
confidence: 95%
“…Roberts and Rosier (1993) adopted a single-layer model because of the lack of changes in values of g s , temperature and vapour pressure deficit with depth in the canopies. Transpiration was very sensitive to the value of L and largely Table 6 Values of maximum stomatal conductance (g smax ) maximum photosynthesis rates (A max ) maximum rates of carboxylation activity (V cmax ) and rates of electron transport at saturating irradiance (J max ) for selected Eucalyptus species This Table is compiled from data published by Grassi et al (2002), Kirschbaum and Farquhar (1984), Kirschbaum and Tompkins (1990), Kuppers et al (1987), Dye and Olbrich (1993), Roberts and Rosier (1993), Sheriff and Nambiar (1991), Sheriff (1992), Wullschleger (1993), Eamus et al (1995), David et al (1997), Eamus and Cole (1997), Myers et al (1997), Kallarackal and Somen (1997), Mielke et al (1999), White et al (1999White et al ( , 2000, James and Bell (2000), Clearwater and Meinzer (2001), Close and Beadle (2003). insensitive to changes in available energy, temperature and g b .…”
Section: Transpirationmentioning
confidence: 99%